STUDENTS’ PERCEPTION OF BLENDED LEARNING ACTIVITY DURING POST COVID-19 - Ayunda . Wulandari (LINGUISTIK TERAPAN, 2023)
Covid-19 played a major role in changing the education system in Indonesia. One of the changes caused by Covid-19 is the use of blended learning during the transition period after the pandemic. This study aims to investigate how students' perceptions of blended learning are enforced. As many as 6 students from the Department of English Applied Linguistics, Medan State University were involved in this study. The results of this study indicate that students show a positive attitude towards blended learning such as continuing to attend lectures that are held online or offline. In addition, students also feel happy and enthusiastic when learning online and offline. From the cognitive aspect, students show positive perceptions as long as they carry out lectures with blended learning activities. Students get a lot of new experiences in learning using a combination of face-to-face and online learning which is carried out for 16 meetings. The researcher concludes that, blended learning has an impact on behavioral aspects, emotional aspects and cognitive aspects in the English language teaching learning process. Researchers suggest further research on the effectiveness of blended learning activities.